Results of treatment of congenital hypoplasia of metatarsal bones by transosseous osteosynthesis after Ilizarov - Saliev, Murod; Ravshanov, Shaukat; Djabborberganov, Olim; Kholov, Zafar; Khujanazarov, Ilkhom; Kаdyrоv Sanjar (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
Brachymetatarsia is one of podiatric problems, which have been insufficiently covered in medical literature. Surgery is the main method for treating the above pathology. On the basis of the use of distraction technology according to Ilizarov the authors developed a method for lengthening the metatarsals. From 2006 to 2013, 34 female patients (53 feet) with brachymetatarsia were operated on. Long-term results of the treatment were evaluated by the AOFAS scale and achieved 89.2 ± 9.5 points. In all patients their lengthened segment was consolidated. The developed technique of transosseous osteosynthesis for brachymetatarsia made it possible to restore the length of metatarsals and weight-bearing capacity of the anterior foot in 80.6 % of cases. A partial loss of lengthening up to5 mmwithout any essential worsening of results was recorded in 5 patients. Thus, the suggested technique makes it possible to extend and supervise the direction of shortened metatarsals and is effective in treatment of brachymetatarsias.